Program Bimbingan Berbasis Neuro Linguistic Programming untuk Mereduksi Distres pada Peserta Didik di Jenjang Pendidikan SD sampai PT - Juntika Nurihsan (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2008)
Abstract: The purpose of the present study is to formulate a Neuro Linguistic Programming (NLP)-Based Counseling Program to reduce the distress experienced by elementary-through-higher-education students. This research employed a quantitative and qualitative approach. Results of this research found that NLP-based counseling program was effective to reduce the distress experienced by students of elementary school up to students of higher education levels.